Azadirachta indica A. Juss. (Neem) : Reproductive Studies in Relation to Kinetin Application - Sabharwal, Suhani; Dhir, K. K. (Indian Forester, 2009)
The in-vivo morpho-physiological responses to kinetin application in Neem (Azadirachta indica A. Juss.) were studied during three consecutive annual reproductive flushes from bud development onwards to seed set (prior standardization with endogenous levels). The number of buds and flowers per inflorescence was higher in treated branches as compared to the control. Physiological responses were observed to be kinetin-specific. Year 1 sample proteins, total sugars and reducing sugars measured higher following kinetin at 0.5 mM as compared to kinetin at 0.2 mM. The response to year 2 treatments was even better, being significant in 0.5 mM kinetin samples. Year 3 kinetin treatments produced poor flowering response, poor juvenility and low contents of the above compounds as compared to the control. The enzyme assay measuring the activities of invertase, protease, acid- and alkaline phosphatases wasconsistent with the biochemical responses to the kinetin treatments. In control, a shorter regeneration phase seems to lead to lower productivity in terms of floral inflorescence and fruit set. Therefore, it is suggested that the application of kinetin may regulate the reproductive phase resulting in improved organ-biomolecule production.